Postfunctionalization of polyoxometalates: an efficient strategy to construct organic–inorganic zwitterions1. Issue 38 (14th October 2015) - Lv, Chunlin; Hu, Junjie; Khan, Rao Naumaan Nasim; Zhang, Jin; Wei, Yongge
<x xml:space="preserve">Abstract</x> A class of monoorganoimido-substituted hexamolybdates containing a pyridine group have been firstly synthesized. Furthermore, a reaction protocol of alkylation based on the resulting pyridine-functionalized hexamolybdates has been developed, with which a type of zwitterionic clusters has been successfully obtained.